ALTERNATIF DESAIN STRUKTUR ATAS JEMBATAN RANGKA BAJA TIPE HALF THROUGH ARCH PADA JEMBATAN TRISULA BLITAR, JAWA TIMUR - Ester Priskasari; Kartika, Deviani; Vincentius Ivan Gandhi; Wahyu Bangkit Pangestuaji (Institut Teknologi Nasional Malang, 2022)
The bridge is an important infrastructure in the transportation system, namely as a means of crossing the river, as well as connecting between cliffs. The bridge has various shapes, one of which is a curved bridge with cables. Arch bridge is suitable for trident bridge because it has a long span. Through this thesis, the author tries to plan an alternative building over an existing bridge with a curve type. Preliminary planning data includes the total length of the existing bridge 150 m wide by 9 m. The planning method used is LRFD (Load Resistance Factor Design) and uses the Staad Pro v8i assist program. In this planning the author planned floor plates, elongated girders, transverse girders, parent girders, wind bonds, cables, joints and elastomers. From the results of the analysis obtained the structure of the building over the bridge for floor plates using the principal bones D10-200 and reinforcements for D13-200, the elongated steel gelagar profile WF 500 x 200 x 10 x 16, the steel transverse gelagar profile WF 800 x 350 x 16 x 36, the parent steel gelagar profile WF 700 x 300 x 13 x 24, steel steel bond double profile L250 x 250 x 35, for the dimensions of dyform cable D38, for laying using elastomer size 120 cm long, width 120 cm, height 26 cm